Substrate damage in ion-implanted (100) germanium after extended ms flash lamp annealing: Origins and suppression. (February 2021) - Skarlatos, D.; Velessiotis, D.; Skoulikidou, M.C.; Ioannou-Sougleridis, V.; Vouroutzis, N.Z.; Stoemenos, J.
Abstract: In this work, the surface damage induced in ion-implanted (100) Ge after extended (20 ms) flash lamp annealing (FLA) at 800–850 °C is investigated and discussed using combined results from scanning electron microscopy, transmission electron microscopy and atomic force microscopy. The induced surface damage has a variety of morphologies including shallow semi-spherical craters, large rectangular-base pyramids with protrusions, and inverted hollow square-base pyramids. The dominant defect morphology depends on the implanted species, the implantation conditions, the flash lamp annealing temperature, as well as on the capping layer used for the Ge surface protection. These results are interpreted using and adapting models developed to describe similar phenomena that take place during flash lamp annealing in Si. From a technological point of view, the most important outcome of this study is that nitrogen co-implantation enhances significantly the robustness of the Ge surface layer, as revealed by the suppression of the induced damage in all cases. Nitrogen co-implants appear to extend the flash lamp annealing thermal budget envelope, which could be useful to achieve a higher level of donor activation in Ge.